Challenges and Strategies of Dayak Entrepreneurs in Modernization: An Accounting Perspective - Novriyandana, Rifqi; Damayanti, Ratna Ayu; Said, Darwis; Rijal, Muhammad (International Ecsis Association, 2024)
Over the years, Dayak groups in Central Kalimantan, especially the Ngaju Dayak tribe, have operated in line with their traditional norms and expertise, preserving their cultural identity in the face of modern challenges. However, the pressures of technology and globalization often impede their ability to maintain business sustainability, creating a complex dynamic between tradition and adaptation. The Ngaju Dayak culture is characterized by robust ideals embedded in everyday life, such as solidarity, reverence for the environment, and cooperation. These traditional values significantly shape their daily lives and extend into their commercial practices. These cultural values deeply influence corporate practices, shaping thought processes and decision-making strategies within their businesses. By adhering to these principles, Ngaju Dayak entrepreneurs foster a sense of trust and collective well-being, which strengthens community bonds and supports business activities. The research methodology employed in this study was qualitative, involving in-depth interviews with 30 informants. The informants were selected based on their involvement in entrepreneurship and their ability to represent the diverse perspectives of the Ngaju Dayak community. The findings reveal that ethnic entrepreneurship among the Ngaju Dayak is intricately linked to both economic factors and enduring cultural values. Their cultural principles not only guide their business practices but also enhance the connection between ethnic entrepreneurship and broader corporate aspirations, ensuring that their businesses remain sustainable while staying true to their cultural heritage. This research underscores the importance of integrating cultural values into modern entrepreneurial strategies to foster resilience and sustainability.